Gambaran Tingkat Pengetahuan Masyarakat tentang Dagusibu Obat di Desa Gentan Baki Sukoharjo - Prasetyani, Dina; Anggraini, Truly Dian (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
“Get, Use, Save, and Discard” which is commonly abbreviated as DAGUSIBU is a program within the Drug Awareness Family Movement initiated by the Indonesian Pharmacist Association in achieving public understanding and awareness of the correct use of drugs. Improper drug disposal systems are a global concern, a problem that can arise as a result of improper drug disposal is that drug compounds can contaminate groundwater. The purpose of this study was to describe the level of public knowledge about DAGUSIBU Drugs in Gentan Baki Village, Sukoharjo. This study used a descriptive research method with a sample of 330 people, namely residents in Gentan Village spread over 11 RTs who met the inclusion and exclusion criteria. The measuring instrument used in this research is a knowledge questionnaire that has been tested for validity with a value in the range of 0.490-0.824 and a reliability test with a value of 0.94. The research results obtained showed that of the 330 respondents, the respondents' knowledge about DAGUSIBU was 83.41% in the